The eyes do not see what the mind does not know : an underreported feature in mature cystic teratoma of the ovary - Wong, Yin Ping; Tan, GC (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Mature cystic teratoma is the commonest ovarian germ cell tumour which accounts for 70% of all benign ovarian neoplasms in the reproductive age groups. Being a pluripotent germ cell tumour, mature cystic teratoma has at least two out of three mature embryonic germ cell components: ectoderm, mesoderm and endoderm. The presence of multiple cystic spaces within the tumour wall, also known as pneumatosis cystoides-like appearance is rarely described but a characteristic feature in cystic teratoma of the ovary. Currently, there is little information concerning the mechanism of its formation. Herein, we described an unusual case of ovarian mature cystic teratoma in a 31-year-old pregnant female with multiple sieve-like areas resembling pneumatosis cystoides of the intestine. Macroscopic and histological examination of the ovary revealed features diagnostic of mature cystic teratoma. Intriguingly, multiple cystic spaces of variable sizes were found within the cyst wall histologically. They were lined partially or completely by foamy histiocytes and foreign body type multinucleated giant cells, exhibiting strong CD68 immunoreactivity. Vascular endothelial markers (CD31 and CD34) and epithelial marker (cytokeratin AE1/AE3) were negative. A diagnosis of mature cystic teratoma with pneumatosis cystoides-like feature was rendered. The patient was discharged well with no signs and symptoms of early labour. The etiopathogenesis of this intriguing histological feature is briefly discussed in this article.